Early Historical Clay Cist Graves at Kalotuwawa (Sri Lanka) - Perera, Nimal (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
Two megalithic cist graves were exposed at Kalotuwawa (Sri Lanka). The cists showed traces of heavy burning and were filled with ashes, charcoal and a few calcinated human bones. Potsherds in the pits belonged to grave goods. The vessels were of Black-and-Red Ware and common Red/Brown Ware. Radiocarbon samples give a date of 135 ± 51 B. C.The article will be available as a PDF in the near future.